Information seeking research needs extension towards tasks and technology - Kalervo Järvelin; Peter Ingwersen (Information Research: An International Electronic Journal)
This paper discusses the research into information seeking and its directions at a general level. We approach this topic by analysis and argumentation based on past research in the domain. We begin by presenting a general model of information seeking and retrieval (IS&R) which is used to derive nine broad dimensions that are needed to analyze IS&R. Past research is then contrasted with the dimensions and shown not to cover the dimensions sufficiently. Based on an analysis of the goals of information seeking research, and a view on human task performance augmentation, it is then shown that information seeking is intimately associated with, and dependent on, other aspects of work; tasks and technology included. This leads to a discussion on design and evaluation frameworks for IS&R, based on which two action lines are proposed: information retrieval research needs extension towards more context and information seeking research needs extension towards tasks and technology.